2005
DOI: 10.1038/sj.ijir.3901391
|View full text |Cite
|
Sign up to set email alerts
|

Association of hypogonadism and type II diabetes in men attending an outpatient erectile dysfunction clinic

Abstract: Patients with diabetes mellitus (DM) were more often hypogonadal than normal fasting glucose subjects. The aim of this investigation is the assessment of characteristics and psychobiological correlates of DM associated with hypogonadism (DMAH). The Structured Interview SIEDY r was used along with several biochemical, psychological and instrumental investigations in a series of more than 1200 patients with erectile dysfunction (ED); 16% of whom with type II DM. Hypogonadism was defined as circulating total test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
140
0
14

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(169 citation statements)
references
References 43 publications
15
140
0
14
Order By: Relevance
“…Endocrine disorders such as low testosterone and changes in hormone receptors may also be associated with diabetes-associated ED. 10,[115][116][117] This broad and complex area of research is, however, beyond the scope of the present review. Figure 1 Mechanisms of endothelial dysfunction in diabetesassociated ED.…”
Section: Resultsmentioning
confidence: 94%
“…Endocrine disorders such as low testosterone and changes in hormone receptors may also be associated with diabetes-associated ED. 10,[115][116][117] This broad and complex area of research is, however, beyond the scope of the present review. Figure 1 Mechanisms of endothelial dysfunction in diabetesassociated ED.…”
Section: Resultsmentioning
confidence: 94%
“…53 Diabetes is clearly related to hypogonadism, and studies have shown that 20-50% of men with type 2 diabetes mellitus have low serum total or free testosterone. [54][55][56][57] The low serum testosterone levels are associated with lower serum LH and FSH levels, suggesting that the lower serum testosterone levels is due to hypogonadotropic hypogonadism in type 2…”
Section: Obesity Metabolic Syndrome Type 2 Diabetes Mellitus and Lomentioning
confidence: 99%
“…Patients with Obesity, low testosterone levels and ED M Diaz-Arjonilla et al diabetes mellitus and low testosterone levels had symptoms of reduced libido and mood in addition to ED. 91 In a cross-sectional cohort study, ED was related to metabolic factors, smoking and depression, but only to very low testosterone levels (below 8 nmol l À1 or 230 ng per 100 ml), 92 suggesting that ED is related to serum testosterone levels only when it is significantly below the adult range. 93 A recent study in type 2 diabetes mellitus showed that overt hypogonadism (total serum testosterone o8 nmol l À1 and bioavailable testosterone o2.5 nmol l À1 with clinical symptoms) was present in 17 and 14% of men and that the incidence increases with age.…”
Section: Obesity Metabolic Syndrome Type 2 Diabetes Mellitus and Lomentioning
confidence: 99%
“…9 PE ve/veya erektil disfonksiyon (ED) şikâyeti ile başvuran 822 kişilik bir çalışmada, eşler arasında sorun, iş yerinde hoşnutsuzluk gibi stres altında olanlarda PE ve ED arasında anlamlı korelasyon saptanmıştır. 10 Etiyolojiye yönelik yapılan çalışmalarda; ■ Genetik yatkınlık.…”
Section: Prematüre Ejekülasyon Hastalarında Eşlerin Yaş Evlilik Süreunclassified
“…10 ■ Düşük 5-hidroksitriptamin seviyesi ve/veya 5-hidroksitriptamin 2c reseptör hiposensitivitesi olanlarda ejekülasyon eşiği belki de genetik olarak düşük olmakta ve sonuçta daha çabuk sürede ejekülasyon gerçekleşmektedir. Selektif serotonin gerialım inhibitör (SSRI)'lerinin PE'yi inhibe etmesi de bu teoriyi desteklemektedir.…”
Section: 11unclassified